Effectiveness of E-Modules Based on Problem-Based Learning to Improve Student Learning Outcomes - Farid Hamid Ali; Agus Suyatna; Viyanti Viyanti; Chasyanah Diawati (CV. Rayyan Dwi Bharata, 2023)
Improving the quality of education is important for every educational institution from elementary school to college. In reality, the learning and learning process at school does not go well, especially in the thinking ability of students, thinking ability is a cognitive domain that provides a knowledge process from the knowledge that will be obtained by students. To overcome the difficulties of learning environmental pollution science class VII, it is important to use an approach that facilitates a thorough understanding of the concept. Teachers are facilitators in learning, of course, can provide solutions to problems that occur during the teaching and learning process, 21st century teachers are no longer as teacer centers but as facilitators in the learning process to achieve learning goals. This study aims to determine the effectiveness of problem-based learning-based e-module product development to improve the learning outcomes of seventh grade students of SMP Negeri 1 Blambangan Umpu Way Kanan. This research is a development research using the ADDIE approach, with 30 research samples to test the effectiveness of the product using the N-Gain test. The results of the study can be concluded that the results of the development carried out by researchers on environmental pollution material are known to be very effective e-modules based on problem-based learning to improve the learning outcomes of Science Class VII SMP Negeri 1 Blambangan Umpu Way Kanan with the results of 71% there are changes when before and after using e-module development products.